Small-scale urban design interventions: A framework for deploying cities as resource for mental health and mental health literacy - Müller, Helena; Rehn-Groenendijk, Jonas; Wasmer, Anna (Frontiers in Psychology, 2023)
With roughly half of the global population living in cities, urban environments become central to public health often perceived as health risk factors. Indeed, mental disorders show higher incidences in urban contexts compared to rural areas. However, shared urban environments also provide a rich potential to act as a resource for mental health and as a platform to increase mental health literacy. Based on the concepts of salutogenesis and restorative environments, we propose a framework for urban design interventions. It outlines (a) an output level, i.e., preventive and discursive potentials of such interventions to act as biopsychosocial resources, and (b) a process level, i.e., mechanisms of inter- and transdisciplinary collaboration of researchers and citizens in the design process. This approach aims at combining evidence-based, salutogenic, psychosocially-supportive design with a focus on mental health. Implementing low-threshold, resource-efficient options in the existing urban context brings this topic to the public space. Implications for the implementation of such interventions for citizens, researchers, and municipality stakeholders are discussed. This illustrates new directions of research for urban person-environment interactions, public health, and beyond.